Mechanical performance and energy absorption properties of structures combining two Nomex honeycombs. (1st February 2018) - Zhou, Hui; Xu, Ping; Xie, Suchao; Feng, Zhejun; Wang, Da
Highlights: Mechanical performance and energy absorption property of four combinations were investigated. Four combinations of honeycombs offered different advantages and disadvantages in different situations. The combinations with clapboards can be applied as crashworthiness structures. Combinations without clapboards can be applied as cushioning and energy-absorbing structure. The conclusions provide supporting for application and performance optimisation of Nomex honeycombs. Abstract: To study the mechanical performance and energy absorption property of two-layer Nomex honeycombs of different types, compressive tests on different combinations were conducted and the experimental results compared with those from tests on single honeycomb specimens. The types of combinations include combinations of two honeycombs of the same specification without a clapboard (HSSWC), combinations of two honeycombs of the same specification containing a clapboard (HSSCC), combinations of two honeycombs of different specification without a clapboard (HDSWC), and combinations of two honeycombs of different specification containing a clapboard (HDSCC). The results showed that different combinations were suitable for different situations. It was advisable to apply the combinations containing clapboards as crashworthy structures which call for large collapse stress. It is necessary to reduce the initial collapse stress in the damping and energy-absorbing structures, so combinations without clapboards can be used. The structures combining different honeycomb specifications can be adopted to control the ordered deformation and ladder energy levels.